'A development of practical Catholic Emancipation': laying the foundations for the Roman Catholic urban landscape, 1850–1900. (29th May 2018) - NICGHABHANN, NIAMH
ABSTRACT: The infrastructures of devotion and religious worship in Ireland changed dramatically during the course of the nineteenth century. This article examines the foundation stone ceremonies that marked the beginning of several large-scale building Roman Catholic church building projects between 1850 and 1900, and in particular considers the extent to which these highly visible and ceremonial events prefigured the more permanent occupation of public space by the new buildings. These foundation stone ceremonies were complex events that reflected contemporary political issues such as land rights as much as they engaged with the spiritual concerns of the Roman Catholic congregations in Ireland during this period.